Modul Pembelajaran Etnosains: Integrasi Agroindustri Lokal dalam Pembelajaran IPA untuk Meningkatkan Literasi Ekologi dan Kewirausahaan Siswa - Jumriani Jumriani; Novia Sandra Dewi; Wahyuni Adam; Alif Ridhai; Nurzakinah Nurzakinah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
Ethnoscience based science learning has gained increasing attention as an approach to contextualize science and integrate local wisdom into formal education. The study aimed to develop an ethnoscience teaching module integrating the local agroindustrial potential to improve students’ ecological literacy and entrepreneurial attitudes. The research employed a Research and Development (R&D) approach using the 4-D models. The define stage involved needs analysis, the findings indicated that science learning remains conventional and has not yet utilized local potentials such as coffee, cocoa, patchouli oil, coconut oil, palm sugar, and palm oil as contextual learning resources. The design stage produced a module framework linking science concepts (carbon compounds, changes in matter, and green chemistry) with local commodity processing practices. The module was designed using an ethnoscience approach and was complemented with entrepreneurship projects and ecological literacy activities. In the development stage, expert validation yielded an average score of 3.7 (highly valid) and limited trial involving 23 students resulted in a practicality and readability score of 95% (highly practical). These findings imply that ethnoscience based modules integrating local agroindustry can serve as contextual and transferable learning resources to support students’ understanding of ecological literacy and entrepreneurial skills in regions with similar agroindustrial characteristics.